Green Logistics Approach in Bioethanol Conversion from Potato Starch in Central Java. (August 2019) - Yusianto, R; Marimin,; Suprihatin,; Hardjomidjojo, H
Abstract: The demand for alternative sources of fossil fuel energy in Indonesia is increasing. One alternative to fossil fuels is bioethanol. Potato skin starch can be a raw material for making bioethanol. Potato skin contains starch, cellulose, hemicellulose, lignin and sugar. Bioethanol can be used must go through several stages, including the logistics system. Logistics activities require transportation, material handling equipment, and warehouses. In Indonesia, transportation sector which is the biggest user of fuel actually receives fuel subsidies. Bioethanol is the most appropriate alternative solution to replace gasoline. In processing, bioethanol through five stages, namely, potato skin starch, raw material logistics, processing bioethanol, delivery process and customer. This study presents green logistics model of potato transportation with a cost model and GWP. The results of the study show that the green logistics model by looking at the total costs and environmental impacts can be used as a reference in developing environmentally friendly bioethanol production in the future.